Psychological Motives in the Conduct of Monetary Policy: Delayed Actions - Berument, Hakan; Doğan, Nükhet; Şahin, Göktuğ (Fırat University, 2024)
The effects of increasing versus decreasing interest rates on economic performance differ in an economy. In Türkiye, members of the Central Bank’s Monetary Policy Committee are criticized by governments when interest rates are increased and praised when they are decreased. Therefore, we examine whether there is a psychological motive for the Committee’s actions when interest rates need to be increased or decreased. In this study, Bai and Ng’s symmetry tests are applied to the Central Bank’s interest rate decisions. The results show that Türkiye’s short-term interest rate changes are positively skewed, which suggests that the Central Bank is more likely to decrease rather than increase interest rates when needed. Thus, interest rate increases occur less frequently than decreases, as suggested by positive skewness (third moment), and have larger magnitudes in raises, as suggested by hyperskewness (fifth moment). Implementing legal and institutional reforms to protect members of the Monetary Policy Committee from political pressure could therefore be a vital step. This could include terms of appointment that ensure longer tenure and protection against arbitrary dismissal; clear legal mandates that prioritize economic objectives such as price stability and financial stability; and statutory provisions that limit the government’s ability to interfere in monetary policy decisions.

Faiz oranlarını artırmanın ve azaltmanın ekonomik performans üzerindeki etkileri farklılık göstermektedir. Türkiye'de Merkez Bankası Para Politikası Kurulu üyeleri, faiz oranları artırıldığında hükümet tarafından eleştirilmekte, düşürüldüğünde ise takdir edilmektedirler. Bu nedenle çalışmada, faiz oranlarının artırılması veya azaltılması gerektiğinde Kurul'un eylemleri için psikolojik bir güdü olup olmadığı incelenmektedir. Bu çalışmada, Bai ve Ng (2005) simetri testleri Merkez Bankası'nın faiz oranı kararlarına uygulanmıştır. Sonuçlar, Türkiye'nin kısa vadeli faiz oranlarındaki değişikliklerin pozitif çarpık olduğunu göstermekte, bu da Merkez Bankası'nın gerektiğinde faiz oranlarını artırmaktan ziyade düşürme olasılığının daha yüksek olduğunu göstermektedir. Dolayısıyla, pozitif çarpıklığın (üçüncü moment) işaret ettiği gibi, faiz oranı artışları düşüşlerden daha az sıklıkta gerçekleşmekte ve hiperçarpıklığın (beşinci moment) işaret ettiği gibi artışlar daha ölçekli büyüklüklere sahip olmaktadır. Para Politikası Kurulu üyelerini siyasi baskıdan korumak için yasal ve kurumsal reformların uygulanması bu nedenle önemli bir adım olarak düşünülmektedir. Ayrıca ilgili düzenlemelerin, daha uzun görev süresi ve keyfi görevden almaya karşı koruma sağlayan atama şartlarını; fiyat istikrarı ve finansal istikrar gibi ekonomik hedeflere öncelik veren açık yasal yetkileri ve hükümetin para politikası kararlarına müdahale etme kabiliyetini sınırlayan yasal hükümleri dahil edebilecek düzeyde olması önerilmektedir.
Para Politikasının Yürütülmesinde Psikolojik Motivasyonlar: Gecikmiş Eylemler
Keywords: Monetary Policy; Para Politikası; Monetary-Banking; Para-Bankacılık